Development of Meandered Microstrip Antenna for RFID Application - Agus Sria Warman, Vista; Anwar, Radial; Wahyu, Yuyu (IJAIT (International Journal of Applied Information Technology), 2018)
Antenna miniaturization has become one important research, especially in mobile communication technology development. This paper presents the development of a miniaturized antenna for RFID application (924 MHz). Meandering technique has been adopted to create a geometrically small antenna relative to its operating frequency. Measurement result shows that the fabricated antenna inherits low return loss, down to -25.915 dB. The geometry of the antenna is 25.54 mm x 16 mm, which is much smaller than its resonance wavelength (0.079? x 0.049?). The measured gain is relatively small, of about -12 dBi. Nevertheless, the obtained parameters are acceptable since the antenna is meant for near field communication application.